Dapagliflozin ameliorates intestinal stem cell aging by regulating the MAPK signaling pathway in Drosophila - Yan, Jinhua; Feng, Chenxi; Zhang, Hanmei; Luo, Ting; Chen, Haiyang; Chen, Haiou (Frontiers in Cell and Developmental Biology, 2025)
IntroductionIntestinal stem cells (ISCs) possess the ability to self-renew and differentiate, which is essential for maintaining intestinal tissue homeostasis. However, their functionality significantly declines with age, leading to diminished tissue regeneration and an increased risk of age-associated diseases.MethodsThis study investigates the effects of Dapagliflozin (DAPA), a novel insulin sensitizer and SGLT2 inhibitor, on aging ISCs using the Drosophila melanogaster model. Our findings demonstrate that DAPA can inhibit the MAPK signaling pathway, as confirmed by network pharmacology analysis and molecular docking experiments.ResultsDAPA ameliorates ISC aging, improves intestinal function (including enhanced fecal excretion, restored intestinal barrier integrity and acid-base balance), and enhances healthspan. These results highlight the potential of DAPA as an anti-aging therapeutic agent.DiscussionThis study provides new evidence for the application of DAPA as an anti-aging treatment.